Determination of train vehicle speed using Fibre Bragg Grating sensors for railway application - Nur Shufinah Suhaimi,; Meor Iqram Meor Ahmad,; Mohd Zaki Nuawi,; Mohd Hafizi Zohari,; Ahmad Kamal Ariffin,; Aidie Zeid Muhammad Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The average speed of the train can be determined by dividing the distance by the time taken to reach the targeted destination. Nevertheless, in the process of railroad travel, the pace of the train can either slow down or speed up depending on the circumstances. It is essential to conduct research into the speed of the railroad in particular conditions to ascertain what speed is appropriate for the railroad to run safely under certain conditions. This study is currently being conducted using Fibre Bragg Grating (FBG) sensors to determine the speed of the train at a specific point. Three different specific points are chosen. The speed is calculated by dividing the distance between two wheels on one bogie by the time between the two peaks representing the two wheels on one bogie. The train traveling between each point exhibits three different speed behaviours. It is currently found that the average speed at location 1 is 49.71 km/h, and the train is decelerating. At location 2, the average speed is 66.21 km/h, and the train moves at a constant speed. Lastly, at location 3, the average speed is 40.18 km/h, and the train is accelerating. In addition, the wavelength shifting signal can be utilized to count the train’s axles. In this experiment, the train consists of 9 bogies with 18 sets of wheels. Therefore, this experiment demonstrates that FBG sensors can be used to determine the speed of the train at a certain location.